Effects of maternal, gestational, and perinatal variables on neonatal line width observed in a modern UK birth cohort. Issue 2 (10th March 2020) - Hassett, Brenna R.; Dean, M. Christopher; Ring, Susan; Atkinson, Charlotte; Ness, Andrew R.; Humphrey, Louise
Abstract: Objectives: The objective of this study was to explore potential relationships between neonatal line (NNL) width and early life history variables such as maternal health, gestation, the birth process, and perinatal health. Materials and methods: Histological thin sections of deciduous canines were studied from 71 children from the Avon Longitudinal Study of Parents and Children (ALSPAC). The width of the NNL was measured in three locations on the tooth crown using spatial mapping techniques (ArcGIS) from digital images from an Olympus VS‐120 microscope. Life history variables were collected prospectively through a combination of clinical observations and questionnaires. Results: Infants born late term or post term had narrower neonatal lines than those born prematurely or at full term. Infants born in Autumn (September to November) had narrower NNLs than those born at other times of year. NNLs in infants born to mothers with hypertension were wider than those without. Infants resuscitated at birth or born to obese mothers had narrower NNLs than those that were not. There was no association between NNL width and either the type or duration of delivery. Discussion: The NNL in enamel is an irregular accentuated line, but the factors underlying its formation and width remain unclear. In contrast to some previous studies, we found no association between wider NNLs and long or difficult births. Instead, we found that the width of the neonatal line NNL varied in relation to parameters that reflected the prenatal environment and length of gestation.